Między alegorią a typologią. Uwagi o hermeneutyce Orygenesa - Domaradzki, Mikołaj (Polskie Towarzystwo Religioznawcze, 2011)
Mikołaj Domaradzki – ALLEGORY VERSUS TYPOLOGY. SOME REMARKS ON ORIGEN’S HERMENEUTICS The presented paper examines Origen’s non-literal and non-anthropomorphic interpretation of the Scripture. While the philosopher’s theological hermeneutics is being situated within the context of modern distinction between allegory and typology, the article shows the distinction to be completely alien to Origen. Consequently, it is argued here that Origen’s hermeneutics should not be classified as merely „allegorical” or „typological”. Although one can find in Origen utterances that actually do invite the label of an allegorical and/or typological exegesis, their selection and evaluation seems to be invariably conditioned by the interpreter’s personal perspective. Accordingly, the paper suggests that Origen’s theological hermeneutics is best characterized as a form of rational criticism leveled against literalism and anthropomorphism. When seen in this light, Origen’s theory of inter-pretation transpires to be profoundly anti-fundamentalist, since it heralds a gradual departure from orthodox and nationalistic reading of the Holy Books.